Social media and professional development: a systematic review - Carles Bruguera; Montse Guitert; Teresa Romeu (Association for Learning Technology, 2019)
The great popularisation of social media at the beginning of the 21st century has led to the production of many empirical studies in an attempt to explore the opportunities these platforms provide for different activities, such as learning and updating for professionals. This study aims to identify and summarise the main characteristics of research into social media and professional development published between 2013 and 2017. We analysed the years, journals, conceptual background, research methodologies, data collection tools, professional disciplines, educational contexts, types of social media and characteristics of social media that can generate learning opportunities. A total of 44 articles were selected and analysed from peer-reviewed journals. Findings revealed that (1) an upward trend with respect to research on social media and professional development; (2) surveys were the main research method for collecting data about social media; (3) health and education sciences are the most studied fields of knowledge; (4) there is a special interest in the study of social media in informal learning contexts; (5) Twitter is the most studied social media platform and (6) social media seems to be a sustainable support for professional development due to its open, social and flexible nature. Implications of findings for future research are also discussed.